Investigating The Protective Capabilities of Earthquake Desks Through Compression and Shock Table Tests - Veletzos, Marc J; Sijapati, Sweata; Malla, Prayash; Tiwari, Kirty; Joshi, Dinesh; Stenner, Heidi; Bruno, Ido; Brutter, Arthur; Kumar, Hari; Motra, Gokarna B; et al. (Journal of Science and Engineering, 2026)
This paper describes a series of physical tests conducted on Earthquake (EQ) Desks manufactured in Nepal to determine their capacity and improve the understanding of their performance under falling debris during a seismic event. The testing program included five vertical compression (static) tests and a dynamic shock table test. The desks tested included both secondary (high) school and primary (elementary) school sizes, with some featuring new plywood panel "side protection" to evaluate its effectiveness. The compression tests were aimed to quantify the vertical load and displacement capacities of the desks, as well as their energy absorption capabilities. Results indicated that the desk capacity is highly dependent on the loading application, with a minimum elastic load capacity of 45.7 kN, a minimum peak load capacity of 98.2 kN, a minimum peak displacement capacity of 92 mm, a minimum elastic energy capacity of 0.28 kJ, and a minimum total energy capacity of 7.05 kJ. During the dynamic shock table test, six EQ Desks were subjected to the complete collapse of a full- scale mock-up school classroom. The single-story mock-up building was constructed with two unreinforced stone masonry walls with mud mortar and slate stone roof. The other two sides of the structure were left open. Observations revealed that EQ Desks experienced impacts from stone walls and roofs separately. A significant finding was that although the lateral debris wave pushed some desks, none toppled. EQ Desks with side protection demonstrated a reduction in debris entering the "safety- zone" below the desk. Importantly, all EQ Desks sustained only minor cosmetic damage to the plywood desktop and edging, successfully maintaining their full "safety-zone" throughout the tests, and no simulated occupants (water containers) were punctured, indicating non-lethal injury to children. The vertical demands observed during the shock table test were found to be below the minimum elastic load and energy capacities of the desks. These findings confirm the robust performance of Nepal-built EQ Desks, supporting their appropriateness as a protective solution in single-story stone masonry buildings and potentially two-story structures.